Effectiveness of WhatsApp based debunking reminders on follow-up visit attendance for individuals with hypertension: a randomized controlled trial in India - Favaretti, Caterina; Subramonia Pillai, Vasanthi; Murthy, Seema; Chandrasekar, Adithi; Yan, Shirley D.; Sulaiman, Huma; Gautam, Atul; Kaur, Baljit; Ali, Mohammed K.; McConnell, Margaret; Sudharsanan, Nikkil (BMC public health, 2024)
Individuals with high blood pressure in India often miss essential follow-up visits. Missed visits contribute to gaps across the hypertension care continuum and preventable cardiovascular disease. Widespread misconceptions around hypertension care and treatment may contribute to low follow-up attendance rates, but to date, there is limited evidence of the effect of interventions to debunk such misconceptions on health-seeking behavior. We conducted a randomized controlled trial to measure whether combining information debunking commonly-held misconceptions with a standard reminder reduces missed follow-up visits among individuals with high blood pressure and investigated whether any observed effect was moderated through belief change.
Gesehen am 07.03.2025